2001
DOI: 10.1021/jp002778c
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Particle Morphology and Crystallite Size on the Upconversion Luminescence Properties of Erbium and Ytterbium Co-doped Yttrium Oxide Phosphors

Abstract: Phosphor particles (ca. 60 nm in size) of yttrium oxide co-doped with Er 3+ and Yb 3+ ions were prepared by a precipitation method in the presence of EDTA. Their physical properties were compared to much larger particles (ca. 600-800 nm in size) prepared in the absence of EDTA. All of the particles were shown to have crystallized in the cubic phase, and all exhibited blue, blue-green, and green-yellow upconversion emission when excited with laser light of wavelength equal to 632.8 nm. These upconversion emissi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

8
208
2

Year Published

2009
2009
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 245 publications
(218 citation statements)
references
References 36 publications
8
208
2
Order By: Relevance
“…Two emission bands were also observed near 550 and 680 nm in the PL spectra of the NPs (Figs. 21d and e), and the intensity of the red emission was greater than that in the green region due to the efficient energy transfer from the Yb co-dopant to the Er luminescence center [81]. These results confirmed that Yb co-doped CeO 2 :Er MARIMO NPs with efficient UC emission were successfully prepared via the one-pot, single-step reaction in scMeOH.…”
Section: One-pot Single-step Synthesis Of Element-doped Marimo Nps Insupporting
confidence: 63%
See 1 more Smart Citation
“…Two emission bands were also observed near 550 and 680 nm in the PL spectra of the NPs (Figs. 21d and e), and the intensity of the red emission was greater than that in the green region due to the efficient energy transfer from the Yb co-dopant to the Er luminescence center [81]. These results confirmed that Yb co-doped CeO 2 :Er MARIMO NPs with efficient UC emission were successfully prepared via the one-pot, single-step reaction in scMeOH.…”
Section: One-pot Single-step Synthesis Of Element-doped Marimo Nps Insupporting
confidence: 63%
“…Next, to further explore the versatility of the one-pot, one-step synthetic procedure, the preparation of Er, Yb co-doped nanoparticles was attempted [81]. Yb co-doped CeO 2 :Er MARIMO NPs, CeO 2 :Er,Yb (100:1:1), were [79] (Figs.…”
Section: One-pot Single-step Synthesis Of Element-doped Marimo Nps Inmentioning
confidence: 99%
“…where W is the coating weight, ρ is the density of crystalline phosphor material, 5.6 g/cm 3 for ZnO:Zn and 5.0 g/cm 3 for Y 2 O 3 :Eu, and B is the packing density in the layer. An attempt to determine the packing density from SEM pictures recorded at high-tilt angles yielded R207 an estimated value of about 70%.…”
Section: Presented Inmentioning
confidence: 99%
“…[1][2][3][4][5] More recently we have given an account on a CL study on double layers of zinc doped zinc oxide (ZnO:Zn) and nanometer sized (NS) europium doped yttrium oxide particles (Y 2 O 3 :Eu). 6 The objective of that study was to increase the light output of phosphor layers by making double layers of low and high voltage phosphors.…”
mentioning
confidence: 99%
“…In recent years, there is a great interest in the investigation of up-conversion luminescence materials due to the wide range of their applications, such as in solid state lasers, screen displays, sensors, optical data storage, fluorescent labels for sensitive detection of bio-molecules and telecommunications [2][3][4][5][6]. The most commonly used activator is trivalent rare earth ion Er 3+ since it posses the metastable 4 I 9/2 and 4 I 11/2 levels that can be filled using the low-cost high-power diode laser of 980 nm.…”
mentioning
confidence: 99%